2010
DOI: 10.1590/s1519-69842010000500007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of populations of broad-snouted caiman (Caiman latirostris, Daudin 1802, Alligatoridae) in the São Francisco River basin, Brazil

Abstract: We surveyed populations of the broad-snouted caiman, Caiman latirostris, throughout the São Francisco River basin, from Três Marias reservoir, State of Minas Gerais, to the river delta, at the boarder of Sergipe and Alagoas states. We registered the occurrence of crocodilians in 61% of all surveyed localities (n = 64), in which the presence of C. latirostris was confirmed in 44% of the surveyed sites. Caimans occurred in both lentic and lotic habitats, although there was a preference for small dams, oxbow lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
2
Order By: Relevance
“…The Broad-snouted Caiman has a wide latitudinal distribution in South America (between 5°S and 32°S; Filogonio et al, 2010;Verdade et al, 2010), with the southernmost distribution occurring in Santa Fe province, Argentina (31°S; Simoncini et al, 2009), where populations have been under management by "Proyecto Yacaré" since 1990 (Larriera, 1990). Proyecto Yacaré in Argentina (Larriera et al, 2008), was undertaken to achieve sustainable use of caimans in wetlands in Northern Santa Fe Province.…”
Section: Introductionmentioning
confidence: 99%
“…The Broad-snouted Caiman has a wide latitudinal distribution in South America (between 5°S and 32°S; Filogonio et al, 2010;Verdade et al, 2010), with the southernmost distribution occurring in Santa Fe province, Argentina (31°S; Simoncini et al, 2009), where populations have been under management by "Proyecto Yacaré" since 1990 (Larriera, 1990). Proyecto Yacaré in Argentina (Larriera et al, 2008), was undertaken to achieve sustainable use of caimans in wetlands in Northern Santa Fe Province.…”
Section: Introductionmentioning
confidence: 99%
“…Populations are the unit of the evolutionary process (Dobzhansky 1970). Conservation genetic efforts should focus on populations to preserve the evolutionary process itself besides the conservation biology aspects.…”
Section: Categorization Lists and Conservation Programsmentioning
confidence: 99%
“…hot climates, and as predators, they are important for the overall balance of their ecosystems (Naish, 2001). Six of the 25 species of alligators worldwide (Pincheira-Donoso et al, 2013) are found in Brazilian territory (Filogonio et al, 2010), and among these is the Pantanal Caiman. Several…”
mentioning
confidence: 99%